The synthesis of nanoscopic Ti based alloys and their effects on the MgH2 system compared with the MgH2 D 0.01Nb2O5 benchmark - Pitt, Mark; Paskevicius, Mark; Webb, C.; Sheppard, Drew; Buckley, Craig; Gray, E. (Elsevier Ltd, 2011)
The MgH2 + 0.02Ti-additive system (additives = 35 nm Ti, 50 nm TiB2, 40 nm TiC, <5 nm TiN, 10 × 40 nm TiO2) has been studied by high-resolution synchrotron X-ray diffraction, after planetary milling and hydrogen (H) cycling. TiB2 and TiN nanoparticles were synthesised mechanochemically whilst other additives were commercially available. The absorption kinetics and temperature programmed desorption (TPD) profiles have been determined, and compared to the benchmark system MgH2 + 0.01Nb2O5 (20 nm). TiC and TiN retain their structures after milling and H cycling. The TiB2 reflections appear compressed in d-spacing, suggesting Mg/Ti exchange has occurred in the TiB2 structure. TiO2 is reduced, commensurate with the formation of MgO, however, the Ti is not evident anywhere in the diffraction pattern. The 35 nm Ti initially forms an fcc Mg47.5Ti52.5 phase during milling, which then phase separates and hydrides to TiH2 and MgH2. At 300 °C, the MgH2 + 0.02 (Ti, TiB2, TiC, TiN, TiO2) samples display equivalent absorption kinetics, which are slightly faster than the MgH2 + 0.01Nb2O5 (20 nm) benchmark. All samples are contaminated with MgO from the use of a ZrO2 vial, and display rapid absorption to ca. 90% of capacity within 20 s at 300 °C. TPD profiles of all samples show peak decreases compared to the pure MgH2 milled sample, with many peak profiles displaying bi-modal splitting.TPD measurements on two separate instruments demonstrate that on a 30 min milling time scale, all samples are highly inhomogenous, and samplings from the exact same batch of milled MgH2 + 0.02Ti-additive can display differences in TPD profiles of up to 30 °C in peak maxima. The most efficient Ti based additive cannot be discerned on this basis, and milling times ≫ 30 min are necessary to obtain homogenous samples, which may lead to artefactual benefits, such as reduction in diffusion distances by powder grinding or formation of dense microstructure. For the hydrogen cycled MgH2 + 0.01Nb2O5 system, we observe a face centred cubic Mg/Nb exchanged Mg0.165Nb0.835O phase, which accounts for ca. 60% of the originally added Nb atoms.